2021
DOI: 10.3389/fcell.2021.664317
|View full text |Cite
|
Sign up to set email alerts
|

Long-Read Sequencing to Unravel Complex Structural Variants of CEP78 Leading to Cone-Rod Dystrophy and Hearing Loss

Abstract: Inactivating variants as well as a missense variant in the centrosomal CEP78 gene have been identified in autosomal recessive cone-rod dystrophy with hearing loss (CRDHL), a rare syndromic inherited retinal disease distinct from Usher syndrome. Apart from this, a complex structural variant (SV) implicating CEP78 has been reported in CRDHL. Here we aimed to expand the genetic architecture of typical CRDHL by the identification of complex SVs of the CEP78 region and characterization of their underlying mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 58 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…Best practices for SV prioritization are evolving, and generally mirror steps used to prioritize SNVs. Few SV-tailored impact predictors have been developed, but a small number of published studies have focused on identifying pathogenic SVs from WES 10 , 11 and WGS 7 , 12 , 13 and have identified a handful of important steps. Removing low-quality SV calls is essential, as short-read SV callers rarely achieve precision above 80% for deletions and 50% for duplications, even at low recall.…”
Section: Introductionmentioning
confidence: 99%
“…Best practices for SV prioritization are evolving, and generally mirror steps used to prioritize SNVs. Few SV-tailored impact predictors have been developed, but a small number of published studies have focused on identifying pathogenic SVs from WES 10 , 11 and WGS 7 , 12 , 13 and have identified a handful of important steps. Removing low-quality SV calls is essential, as short-read SV callers rarely achieve precision above 80% for deletions and 50% for duplications, even at low recall.…”
Section: Introductionmentioning
confidence: 99%
“…CEP78 is a known causative gene for CRDHL syndrome, which is characterized by cone-rod dystrophy and sensorineural hearing loss, with relatively late onset of both ocular and auditory impairments ( 19 22 ). Thus, our proband showed defects in hearing and vision.…”
Section: Resultsmentioning
confidence: 99%
“…To date, several inactivating variants, a missense variant, and two complex structural variants in CEP78 have been identified in individuals with autosomal recessive CRDHL syndrome, a rare syndromic inherited retinal disease accompanied by sensorineural hearing loss (19)(20)(21)(22). In addition, two splicing mutations in CEP78 were identified in two independent families with a mild degree of Usher syndrome, a genetic disorder characterized by the combination of retinitis pigmentosa and sensorineural hearing loss (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the recent elucidation of DYNC2H1 as a cause of inherited ophthalmic conditions was not captured in our initial curation process but can be subsequently included in EyeG2P analysis through addition of a single data line to the released EyeG2P datafile. 25 Our ability to detect disease-causing genomic variants from high-throughput sequencing datasets has expanded in recent years to include complex structural variants, 26,27 exonic deletions and duplications, 28,29 deeply intronic variants causing aberrant splicing, [30][31][32][33] variants in regulatory regions [34][35][36] and complex alleles comprised of combinations of genomic variants common in the general population. 37,38 Here we found that, in addition to characterizing novel exonic variants, EyeG2P is capable of prioritizing these diverse types of disease-causing variation, achieving 99.5% sensitivity in comparison to routine analytical approaches (Figure 1).…”
Section: Discussionmentioning
confidence: 99%